The Influence of BMW Group Energy Strategy Communication on Corporate Image - Jurum Kipke, Jasna; Pirić, Valentina; Manucci, Marina (Promet - Traffic&Transportation, 2004)
This paper deals with the application of BMW Group energystrategy communication in order to build excellent BMWcorporate image worldwide with the purpose of analyzing thecurrent situation regarding this topic on the Croatian car marketas well as analyzing the possible influence of BMW environmentprotection care and energy strategy on BMW corporateimage in the Republic of Croatia.To ensure sufficient supply of energy in order to meet the futureneeds, the BMW’s chosen priorities worldwide are to promoteefficient use of today’s available energy sources and to developinnovative solutions for the future. The company usesthese elements in building the desirable BMW corporate image.On the basis of the conducted surve, it was more than obviousthat these activities still do not play a large role in building agood BMW corporate image among BMW customers in Croatia.Obviously, there is great possibility for the BMW Group toimprove its corporate image in Croatia and on the similar marketsboth with the application of intensive environmental careand the energy strategy communication.